Large mucinous cystic neoplasm of the pancreas during pregnancy: a case report. Issue 7 (8th July 2020) - Carvalho, Lúcia; Ferreira, Tiago; Frutuoso, Luísa; Matos, Leonor; Castro, Tiago; Rodrigues, Domingos; Oliveira, Vera; Gonçalves, Gil; Nora, Mário; Scigliano, Horácio
ABSTRACT: Mucinous cystic neoplasms (MCNs) of the pancreas occurring during pregnancy constitute a rare condition requiring special management due to its large size, malignant potential and the risk of fetal growth restriction. The key points to manage MCNs are to perform a correct diagnosis, accurately evaluate the grade of malignant potential in order to establish the right time for pancreatic surgery and to choose the most appropriate fetal mode of delivery. We describe a case of an incidental abdominal mass detected in a third-trimester pregnant woman. At surgery, a huge pancreatic cystic tumour was found and a distal pancreatectomy with splenic preservation was performed. The histopathological analysis revealed an MCN of the pancreas with low-grade dysplasia. To our knowledge, this is the largest pancreatic MCN detected in a pregnant woman reported in the literature and one of the few successfully resected after vaginal delivery.